Correlation of serum calcium levels with severity and functional outcome in acute ischemic stroke patients - Gupta, Abha; Dubey, Umesh; Kumar, Arvind; Singh, Shailesh (International Journal of Research in Medical Sciences, 2017)
Background: The objective of the study was to study the role of serum calcium levels in accessing the severity and functional outcome in the patients of acute ischemic stroke. Methods: The study included a total of 50 patients of acute ischemic stroke in the age group of 20 to 80 years. The patients were divided into four quartiles as per their serum albumin corrected levels measured during 24 ton 48 hours of incidence of ischemic stroke. The stroke severity was accessed by using National Institutes of Health (NIH) stroke scale and the functional outcome at the time of discharge and after three months of follow up by using modified Rankin scale (mRS). The results were analyzed by using appropriate statistical test. Results: We found that the patients those in higher calcium quartiles (Q3,Q4) had significantly lesser 24-48 hrs stroke severity as compared to those in lower calcium quartiles (Q1,Q2) i.e. in 72.73% in Q3, and 42.86% in Q4 were in mild NIH scale group as compared to 7.69% in Q2 and 0% in Q1. At the time of discharge and at three months follow up functional outcome was significantly better in higher calcium quartile group when compared to lower quartile (>3 mRS score suggestive of poor outcome in 91.66% of Q1, 76.93% in Q2, 27.27% in Q3 and 7.14% in Q4 at the time of discharge and 83.32% in Q1, 76.93 in Q2, 27.27% in Q3 and 7.14% in Q4 at three months of follow up). The correlation analysis showed that this association was statistically significant (p-value <0.01). Conclusions: we conclude that 24 -48 hours calcium levels have strong correlation with severity and functional outcome in acute ischemic stroke patients and hence it can be taken as a marker of severity and prognostic factor in these patients.